Survei minat masyarakat terhadap olahraga teqball di Kalimantan Selatan - Syahban, Arham; Antoni, Despita; Sepriani, Rika; Tri Fitrianto, Ari; Hanafi, Moh. (Universitas Nusantara PGRI Kediri, 2025)
Teqball is a new sport in the world. Since the sport of Teqball entered Indonesia in 2019 until now, it has not shown extraordinary development. This research aims to encourage the public to be interested in actively participating in teqball sports. Interest is needed to realize a sports activity because it causes a sense of interest and enjoyment in participating in sports. The subjects in this study are the people of South Kalimantan, especially Kotabaru Regency, with as many as 87 participants using an incidental sampling technique. The survey method uses a questionnaire that has been validated by experts with a validity value of 0.87 and a reliability of 0.79. A percentage-based quantitative descriptive approach is used in the data processing process using SPSS version 26 software, where a questionnaire containing an indigo Likert scale of 1-5 will be given for assessment. The results show that the average interest score was obtained through a percentage descriptive analysis, where the percentage of attention indicators (75%), the percentage of facility indicators (78%), the percentage of environmental indicators (66%), and the percentage of interest indicators (63%). So it can be concluded in this study that the interest in teqball sports among the people of South Kalimantan is at a high standard.